2017
DOI: 10.1002/ps.4649
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterization of putative structural cuticular proteins in the malaria vector Anopheles sinensis

Abstract: These results establish an information framework for An. sinensis CPs that provides a basis for further molecular research. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
(104 reference statements)
2
10
0
Order By: Relevance
“…The expression of CPAP3-A1, CPAP3-C1, CPAP3-D1 and CPAP3-E2 genes were significantly induced in the oriental fruit fly (Bactrocera dorsalis) by malathion, the main pesticide used against this pest [31]. Interestingly, it has been documented that CP genes were over-expressed in deltamethrin-resistant strains of A. sinensis and Culex pipiens pallens, and pyrethroid-resistant strains of A. stephensi, A. gambiae and A. sinensis [38][39][40]. This indicated that the upregulation of CP genes is linked to insecticide resistance, while only a few of them were evidenced as involved in such a role.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CPAP3-A1, CPAP3-C1, CPAP3-D1 and CPAP3-E2 genes were significantly induced in the oriental fruit fly (Bactrocera dorsalis) by malathion, the main pesticide used against this pest [31]. Interestingly, it has been documented that CP genes were over-expressed in deltamethrin-resistant strains of A. sinensis and Culex pipiens pallens, and pyrethroid-resistant strains of A. stephensi, A. gambiae and A. sinensis [38][39][40]. This indicated that the upregulation of CP genes is linked to insecticide resistance, while only a few of them were evidenced as involved in such a role.…”
Section: Discussionmentioning
confidence: 99%
“…The insect cuticle is a complex exoskeleton which covers all the exposed tissues and protects insects against adverse environmental conditions, forms a physical barrier against the intrusion of pathogens and maintains their movement [14]. It is also the main route of insecticide penetration, and the intake of insecticide can be reduced by thickening or changing the chemical composition of the cuticle [5]. The cuticle is mainly composed of chitin and cuticular proteins (CPs) [69].…”
Section: Introductionmentioning
confidence: 99%
“…Insects possess a large number of cuticle proteins that contain chitin-binding domains and belong to different families [ 189 , 190 , 191 , 192 , 193 ]. Proteins with one or three chitin-binding domains (CBD) are members of the CPAP1 or CPAP3 family (Cuticle Proteins Analogous to Peritrophis) [ 194 , 195 , 196 , 197 , 198 ].…”
Section: The Molecular Toolbox For Natural Chitin Matrix Productionmentioning
confidence: 99%